(3bdGOI GdfMQ aj hajGJ CYjGf GdOgQs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3GdYTQhf GdKGfjI ef GdeGFI GdQGHYI CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROi CHh LYaQ GdWMGhi s
(3BNQgG (B:s
(3BNQg fGbU hChd GdehLhO efg CKfGA JQLeI eMeO Hf YHO GdQMef GdNQSGfi GdeYQha HGdeSYhOi TGQM GdebGeGJ , GdeJhai SfI (B584(3, Hbhdg (B( (3hbYO ai NRGfI cJH Gdhba , hGNJGQ efgG LedI CNPgG de jefYg efgG CMO hbGd GHf GdfLGQ (B) s
(3GdLRA GdKGfi ef GdfSNI faSgGs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
Keywords: (3GdJGQjNs